Individual Differences in Developmental Psychology Early Childhood Mentality - Novi Cahya Dewi (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2021)
As long as human life is never static, from birth to death, humans always experience changes; these changes are known as two kinds of changes: growth, which is increasing size and structure, and second, a development which means progressive, coherent, and orderly changes. Differences influence individual differences in early childhood mental development psychology in cognitive, language skills, motor skills, backgrounds, talents, and learning readiness. Parents who directly educate and shape children's social behavior early tend to continue to survive until the child reaches the next stage of development. Individual attitudes toward others and towards social activities are consistent at every age level. Individual development is a functional change that is qualitative, both from physical and mental functions, as a result of its association with environmental influences. Individual development is indicated by changes that are systematic, progressive, and continuous.